Exploring organic matter, soil enzymes, and fungal communities under land - use intensification in the Argentine Pampas - Barbero, Florencia Magali; Verdenelli, Romina Aylén; Dominchin, María Florencia; Frasier, Ileana; Restovich, Silvina Beatriz; Serri, Dannae Lilia; Campilongo Mancilla, Ernesto Javier; Faggioli, Valeria Soledad; Iriarte, Ana G.; Vargas Gil, Silvina; Meriles, José Manuel (MDPI, 2025)
Intensive land use in the Argentine Pampas has led to soil degradation, yet links between soil organic matter (SOM) composition, enzyme activity, and fungal communities remain unclear. This study compared contrasting ecoregions and land uses: pristine (PI), pasture (PA), crop rotation with cover crops (RO), and monoculture (MO). Infrared spectra showed that PI soils in Anguil had higher absorbance in hydroxyl/amine (3400 cm−1: 0.90 ± 0.08) and carbonyl (1750 cm−1: 0.52 ± 0.12) bands than MO soils (0.47 ± 0.30 and 0.35 ± 0.06; p < 0.05), indicating greater SOM diversity. Pergamino soils showed smaller differences, reflecting site-specific effects. Enzyme activities also responded to land use. In Anguil, xylosidase, β-1,4-N-acetylglucosaminidase, and phosphatase peaked under PI (40, 127, and 443 nmol g−1 h−1). In Pergamino, xylosidase and β-1,4-N-acetylglucosaminidase were higher under PA and PI, indicating enhanced microbial functionality under low disturbance. Fungal composition varied with land use and location: Mortierellomycetes dominated in Pergamino, while Leotiomycetes and Agaricomycetes were more abundant in PI and PA, and Dothideomycetes increased in MO and RO. Despite compositional shifts, fungal diversity changed little. Integrating chemical, biochemical, and molecular indicators revealed how land-use intensification modifies SOM and microbial processes in Pampas soils.